The Future is Now: Hands-On Training and Practical Skills for Medical AI Implementation - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Future is Now: Hands-On Training and Practical Skills for Medical AI Implementation The integration of Artificial Intelligence (AI) into healthcare ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation